2010
DOI: 10.1002/psc.1326
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired peptide nanotubes: deposition technology, basic physics and nanotechnology applications

Abstract: Synthetic peptide monomers can self-assemble into PNM such as nanotubes, nanospheres, hydrogels, etc. which represent a novel class of nanomaterials. Molecular recognition processes lead to the formation of supramolecular PNM ensembles containing crystalline building blocks. Such low-dimensional highly ordered regions create a new physical situation and provide unique physical properties based on electron-hole QC phenomena. In the case of asymmetrical crystalline structure, basic physical phenomena such as lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 62 publications
2
89
0
2
Order By: Relevance
“…This long-range electron transfer thus has been shown to increase electricity production by 10 times (Reguera et al, 2006). Along the same lines, MNWproducing photosynthetic micro-organisms (Gorby et al, 2006;Sure et al, 2015;2016b) may be helpful in improving the efficiency of photosynthetic microbial fuel cells and microbial solar cells (Rosenbaum et al, 2010;Strik et al, 2011).…”
Section: Bioenergymentioning
confidence: 93%
See 1 more Smart Citation
“…This long-range electron transfer thus has been shown to increase electricity production by 10 times (Reguera et al, 2006). Along the same lines, MNWproducing photosynthetic micro-organisms (Gorby et al, 2006;Sure et al, 2015;2016b) may be helpful in improving the efficiency of photosynthetic microbial fuel cells and microbial solar cells (Rosenbaum et al, 2010;Strik et al, 2011).…”
Section: Bioenergymentioning
confidence: 93%
“…Scientists are using peptides and proteins as building blocks for the construction of nanodevices including sensors and drug delivery vehicles (Petrov & Audette, 2012;Rosenman et al, 2011;Scanlon & Aggeli, 2008). Several peptide nanotubes have been built and can be used as a casting module for synthesis of metal nanowires (Reches & Gazit, 2003;Scanlon & Aggeli, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Compared to oligoand polypeptides, short peptides, which are composed of only 2-3 amino acid units, can be easily synthesized on a larger scale, with reduced cost. [3] Bioinspired short peptide nanostructures display exceptional physical properties, such as high rigidity, [9] piezoelectric and nonlinear optical effects, [10][11][12][13][14][15][16] and visible fluorescence. [17,18] In addition, bioinspired peptide nanostructures are used in diverse applications, such as solar energy conversion, [19] drug delivery, [20] ultra-capacitors, [21] and linear and nonlinear optical waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] In particular, the native non-symmetric space group of the dipeptide diphenylalanine (FF) and dileucine (LL) peptide nanotubes (PNT) [24] provides fundamental physical properties, described by tensors of the third rank, such as piezoelectricity and second harmonic generation (SHG). [10][11][12][13][14][15][16] It was shown that heat treatment at T > 150 8C induces irreversible phase transition in FF and LL PNT, wherein all the physical properties and the structure at all levels (molecular, space symmetry, wettability, and morphology) change. [12,15,17] This phase transition also leads to a transition in the crystal symmetry of the FF PNT, from the non-centrosymmetric hexagonal C 6 point group to a centrosymmetric orthorhombic D 2h point group.…”
Section: Introductionmentioning
confidence: 99%
“…Макромолекулы коротких олигонуклеотидов, как и макромолекулы белков не содержат ни центров инверсии, ни зеркальной симметрии. Структурное упорядочение таких систем (в любом масштабе) является результатом низкой симметрии их элементарных ячеек, обладающих винтовой или хиральной асимметрией [11,12]. В спектрах комбинационного рассеяния света таких макромолекул должны наблюдаться сильно перекрывающиеся спектральные вклады, генерируемые большим набором атомов для всех функциональных групп, испытывающих также влияние парных взаимодействий и окружающей среды.…”
unclassified